2004
DOI: 10.1086/383422
|View full text |Cite
|
Sign up to set email alerts
|

A Sound Idea: Phonetic Effects of Brand Names on Consumer Judgments

Abstract: In this article we examine a phenomenon known as sound symbolism, where the sound of a word conveys meanings. Specifically, brand names are composed of individual sounds called phonemes and we investigate how this phonetic structure of brand names affects a consumer's evaluation of products and their underlying attributes. We demonstrate that consumers use information they gather from phonemes in brand names to infer product attributes and to evaluate brands. We also demonstrate that the manner in which phonet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
309
3
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(333 citation statements)
references
References 18 publications
11
309
3
10
Order By: Relevance
“…First, the present study adds to the growing body of research on sound symbolism in marketing and consumer psychology. To the best of the authors' knowledge, the study of sound symbolism has been limited to phonetic symbolism in the marketing literature (Argo, et al, 2010;Coulter & Coulter, 2010;Doyle & Bottomley, 2011;Klink, 2000;Klink & Athaide, 2012;Kuehnl & Mantau, 2013;Lowrey & Shrum, 2007;Shrum, et al, 2012;Yorkston & Menon, 2004). The current study extends this narrow focus to musical stimuli, suggesting that sound symbolism can affect a much wider range of contexts and applications than previously assumed.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, the present study adds to the growing body of research on sound symbolism in marketing and consumer psychology. To the best of the authors' knowledge, the study of sound symbolism has been limited to phonetic symbolism in the marketing literature (Argo, et al, 2010;Coulter & Coulter, 2010;Doyle & Bottomley, 2011;Klink, 2000;Klink & Athaide, 2012;Kuehnl & Mantau, 2013;Lowrey & Shrum, 2007;Shrum, et al, 2012;Yorkston & Menon, 2004). The current study extends this narrow focus to musical stimuli, suggesting that sound symbolism can affect a much wider range of contexts and applications than previously assumed.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Along these lines, Yorkston and Menon (2004) examined how brand names differing in vowel backness affected the expected creaminess of ice cream. Their results suggested that back vowel brand names (e.g., "Frosch") led to higher expectations of product creaminess than did front vowel brand names (e.g., "Frisch").…”
Section: Auditory-gustatory Correspondences and Multisensory Processingmentioning
confidence: 99%
“…It is believed that this effect is driven by the sound of the vowels in the two names [see also 25 for a review]. How food names, and the subsequent food expectations that they may elicit, relate to ratings of food pleasantness has been investigated by Martin Yeomans and his colleagues in Sussex [64]. In one of their studies, three groups of participants were given the same red coloured frozen food to taste.…”
Section: Menu: Pricing and Namingmentioning
confidence: 99%